Transformasi Filantropi Islam Sebagai Model Pemberdayaan Zakat, Infak, Sedekah, Dan Wakaf (ZISWAF) - Sahabi, Ansar; Ajuna, Luqmanul Hakiem (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
Philanthropy is an important thing in Islam. The form of its activities originates from religion which originates from the Qur'an and Hadith, it seems that there are zakat, infaq, alms and waqf institutions which have been improved through the mechanism of ijtihad mediation and as a result have become highly admired, widespread and practiced in the life practices of Muslim society since the beginning Islam is growing. In this article, we examine the Transformation of Islamic Philanthropy which focuses on the Transformation of Islamic Philanthropy as a Model for Empowerment of Zakat, Infaq, Alms, Waqf (Ziswaf). This research is descriptive qualitative in nature, namely analyzing Islamic philanthropy, using the